Estimation of Kostiakov İnfiltration Parameters Using Initial Soil Moisture - Abolfazl Nasserı1 (Journal of Agricultural Sciences)
The Kostiakov equation was extensively used to estimate furrovv Infiltration but it is unadjusted for different field conditions. The Kostiakov infiltration parameters (k and a) were therefore developed as a function of initial soil moisture content and irrigation events in current study. The field experiments comprised two types trials. The first was infiltration measuring at 56 sites över the field for the first irrigation event. The second measurements were at the furrovvs along the same field for five successive irrigation events. İnfiltration measurements were taken by blocked furrovv infiltrometers. Results showed that the averages of k ranged from 272.84 to 733.991 mlm'1min'a and for a were from 0.614 to 0.815. The parameter a was described as a non-linear function of initial soil moisture content and as a logarithmic function of k. The parameter k was developed as a non-linear function of initial soil moisture and irrigation events. Cumulative infiltration from five successive irrigation events were correlated to each others and according to the results cumulative infiltration from each irrigation event can be predicted from the other previous irrigation events.